2020
DOI: 10.5539/gjhs.v12n8p107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drug Abuse and Health Risks Among Undergraduates of Federal Universities in Nigeria

Abstract: OBJECTIVE: The study investigated the effect of drug abuse and health risks among undergraduates of Federal Universities in Nigerian. METHODS: The study adopted a descriptive research design. The sample of the study consisted of four hundred and fifty-eight (458) undergraduates. The study adopted structured questionnaire. Cronbach Alpha Reliability Co-efficient was used to determine the instruments which yielded reliability coefficients of 0.78. Data collected were analyzed using mean and standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, 51.4% of people are hostile to those in positions of power, and 48.6% have dishonest habits. The results of this study are consistent with those of Ofuebe et al (2020), who found that drug abuse has a major effect on people and their families and leads to a wide range of mental and behavioral problems [16]. These shifts alter not just the dynamics between children and their parents, but also the dynamics between children and their siblings in, outside the family, and in all over the community.…”
Section: Resultssupporting
confidence: 92%
“…In addition, 51.4% of people are hostile to those in positions of power, and 48.6% have dishonest habits. The results of this study are consistent with those of Ofuebe et al (2020), who found that drug abuse has a major effect on people and their families and leads to a wide range of mental and behavioral problems [16]. These shifts alter not just the dynamics between children and their parents, but also the dynamics between children and their siblings in, outside the family, and in all over the community.…”
Section: Resultssupporting
confidence: 92%
“…También se relaciona con un estudio llevado a cabo en la Universidad Tecnológica de Pereira (Mosquera et al, 2011), donde se encontró una presencia destacada de drogas en los entornos universitarios, como marihuana (51,3%) y tabaco (67,2%), sin existir control respecto a la comercialización de éstos. Estos resultados se asemejan a estudios realizados en países africanos (Makau et al, 2019;Ifeoma et al, 2020;Ibu y Eru, 2018;Mbuthia et al, 2020), en Asia (Ashraf et al, 2020) y en Estados Unidos (Nunes et al, 2017).…”
Section: Discussionunclassified
“…En países como Kenia y Nigeria, el consumo de tabaco y alcohol prevalece entre los estudiantes universitarios (Makau et al, 2019;Ifeoma et al, 2020;Ibu y Eru, 2018;Mbuthia et al, 2020). En Pakistán, por otro lado, el consumo de marihuana y alcohol en entornos universitarios se ha convertido en una preocupación de salud pública, especialmente entre la población joven, debido a factores como la incertidumbre generada por la violencia arraigada en el país (Ashraf et al, 2020).…”
Section: Introductionunclassified
“…[6][7][8][9] Several other studies reported adverse impacts of drug abuse and addiction on human health and the socio-economy, ranging from chronic diseases, infection, and psychiatric ailment to increased crime and law default. [10][11][12][13][14][15] Given the overwhelming prevalence of drug abuse and robust reports on its adverse effects on human health and socio-economy, [6][7][8][9][10][11][12][13][14][15] providing solutions became the focal point for health professionals and other scientists. Through effective awareness and counselling programs and management centres, behavioural therapies were reported to be potent interventions for different forms of drug abuse and dependence as they help improve individuals' knowledge, awareness and perception of drug abuse.…”
Section: 2023________________________24mentioning
confidence: 99%